ENGLISH LEARNING MEDIA BASED ON INTERACTIVE MULTIMEDIA FOR GRAPHIC TECHNOLOGY STUDENTS - Ika Agustina; Nasrudin Nasrudin; Dewi Maharani (Yayasan Education and Social Center, 2021)
This study aims to design an interactive learning media with Multimedia-based for English Course in the Graphic Technologies study program and test the feasibility. This Interactive Media will encourage students' learning independence, especially in answering the limitations of lectures to learn English independently and intensively wherever they are. The research was carried out at Politeknik Negeri Media Kreatif Medan. The interactive media is developed for English courses for the Graphic technology Study Program students of semester 2 in the 2020/2021 academic year. The study applies the R & D (Research and Development) method by developing educational products of interactive multimedia-based stored on DVDs for English language courses and testing the effectiveness of these products. The data in a learning series is recorded in DVD media with settings based on the syllabus and an outline of English learning following Graphic Technology. The media is validated by some experts in graphic technology, learning media and computer programming, scored as 4.38, or it is classified as good. After validated, the interactive learning media with Multimedia-based is tested to suitable responses to the students; it is shown as the questionnaire reaches 4.37 or categorized as so good or very positive. The research can produce the main output in prototypes interactive media with validated and tested multimedia-based